Impact of Hydraulic Resistance on Spatiotemporal Characteristics of Initial Six Steps When Sprinting Under Varying Loads - Matic Sašek; Žiga Leban; Sara Kranjc; Nejc Šarabon (Journal of Functional Morphology and Kinesiology)
Background: Evaluations of the usability of hydraulic resistance for resisted sprint-training purposes remains rare. Thus, this study compared step-by-step changes in spatiotemporal characteristics during the first 10 m of sprints with varying hydraulic resistance loads. Methods: Fourteen male athletes performed 20 m sprints under minimal (10 N, considered as normal sprint), moderate (100 N), and heavy (150 N) hydraulic resistance loads. Split times at 10 m, contact time (CT), step length (SL), flight time, and step speed (SS) from the first to the sixth step were measured. A two-way repeated measures ANOVA (load × step) and a one-way ANOVA (load) with post hoc comparisons were used to assess the effects on spatiotemporal characteristics and split times, respectively. Results: Under higher loads, the 10 m times were significantly longer (η2 = 0.79). The CT, SL, and SS varied significantly from step to step within all loads (η2 = 0.45, 0.41, and 0.54, respectively). The CT, SL, and SS of the first, fourth, fifth, and sixth steps of normal sprint differed significantly from most steps under moderate and heavy load (Cohen’s d = −3.09 to 5.39). In contrast, the smallest differences were observed between the second and third step of normal sprint and second to sixth steps under heavy load (Cohen’s d = −0.67 to 1.32, and −0.71 to 1.38, respectively). Conclusions: At the same load settings, a hydraulic resistance device induces changes in step characteristics comparable with those of other motorized devices and is therefore a viable option for resisted sprint training. If the goal of the training is to replicate the steps of the initial sprint acceleration phase, ~150 N of hydraulic resistance would be optimal.